URGENSI PEMBENTUKAN PERATURAN DAERAH KEPEMUDAAN SEBAGAI KATALISATOR KOTA PASURUAN LAYAK PEMUDA - Nur Aziz, Adi; Safiudin, Khamdan; Yasmin, Yasmin (Gapenas Publisher, 2025)
Youth represent a strategic group in regional development; however, Pasuruan City has yet to establish a Regional Regulation (Perda) that specifically governs youth affairs. The absence of such regulation has resulted in weak governance, limited formal youth participation, and the lack of integration of youth-related issues into regional development planning. This study employs a literature review method with a descriptive-qualitative approach to examine the urgency of formulating a Youth Regulation as a catalyst toward establishing Pasuruan as a Youth-Friendly City. The findings reveal that a Youth Regulation is critically needed as a legal and policy instrument to build an inclusive, structured, and sustainable youth governance system. It also provides the legal foundation for local policymaking, enhances youth participation in development processes, and supports the fulfillment of Youth-Friendly City indicators as outlined in Ministry of Youth and Sports Regulation No. 11 of 2017. Furthermore, this study identifies several challenges, including weak political commitment and a lack of local data, while also highlighting opportunities such as the strengthening of youth communities and the support of national regulatory frameworks. The study recommends that the Pasuruan City Government promptly initiate the drafting of a Youth Regulation through multi-stakeholder collaboration and the integration of Youth-Friendly City indicators into local development planning documents. The establishment of this regulation is not merely a response to administrative demands but a long-term investment in building a just and sustainable development ecosystem centered on the younger generation.